MURABAHAH (Prinsip dan Mekanismenya Dalam Perbankan Islam) - Hannanong, Ismail (Fakultas Syariah dan Hukum Islam Institut Agama Islam Negeri (IAIN) Parepare, 2017)
Abstract: This paper will discuss the mechanism of murabahah agreement and application in Islamic banking, and compare murabahah finance with fixed interest to banks in several key areas. Islamic banks have used murabahah agreements in financing activities through merchandise and expanded their network of uses. Murabahah finance and higher credit prices therein clearly indicate that there is a time value in financing based on murabahah, which leads though not directly to the acceptance of the time value of money.